Navigating Therapeutic Challenges in Adult-Onset Coats' Disease: Successful Vitrectomy for Tractional Retinal Detachment Following Laser Photocoagulation - Albatool Alqahtani; Faisal Al-Qahtani; Abdullah Al Hilali; Alwaleed Alsulaiman (Department of Ophthalmology, Faculty of Medicine, Universitas Sriwijaya, 2025)
Introduction: Adult-onset Coats' disease, an infrequent variant of idiopathic exudative retinopathy, presents a unique management paradigm. While laser photocoagulation is a primary treatment for the characteristic retinal telangiectasia, it can paradoxically trigger a severe inflammatory and fibrotic cascade, leading to vision-threatening complications. This report addresses a critical clinical question: What is the optimal management strategy when first-line ablative therapy not only fails but leads to iatrogenic tractional retinal detachment? Case presentation: A 35-year-old male presented with a 15-day history of metamorphopsia in his right eye. Best-corrected visual acuity (BCVA) was 20/20. Multimodal imaging confirmed Stage 2B Coats' disease. Following sectoral argon laser photocoagulation, his BCVA declined to a nadir of 20/60. Within two months of laser, optical coherence tomography (OCT) documented the rapid development of an epiretinal membrane and a subsequent superior macular tractional retinal detachment (TRD). A 23-gauge pars plana vitrectomy (PPV) with membrane peeling was performed. Anatomical success was achieved, and at the six-month follow-up, the retina remained attached, and BCVA improved to 20/40. Conclusion: This case demonstrates that laser-induced inflammation can rapidly convert an exudative process into a complex fibro-proliferative state in adult-onset Coats' disease. When confronted with iatrogenic fibrosis, medical management is insufficient. This report validates that timely and definitive surgical intervention with PPV is not merely an option but an essential strategy for reversing the disease trajectory, achieving anatomical restoration, and salvaging vision.